Wellness tourism: Evaluating destination attributes for tourism planning in a competitive segment market - Didascalou, E.; Lagos, D.; Nastos, P. (Tourismos, 2009)
The purpose of the present study is to identify the various factors that decision makers must take into account when ranking destinations for placing a spa resort/hotel in the thriving health and wellness industry. The study will suggest a decision support system (DSS) based on key factors as climate, tourism development and attractions. The DSS, using a computer based information system, will evaluate the aforementioned factors and will propose a hierarchical structure for rating destinations, useful for private or public planners in the wellness market. The research categorized the prefectures of Ahaia, Arkadia, Ilia, Korinthia, Messinia in the region of Peloponnese. © University of the Aegean.
Keywords: Analytical hierarchy process; Climate; Spa/health/wellness tourism